Improving Strength and Quality of Epitendinous Repairs. (July 2020) - Farinas, Angel; Stephanides, Michael; Schneeberger, Steven; Pollins, Alonda; Cardwell, Nancy; Thayer, Wesley P.
Background: Epitendinous sutures not only join the 2 severed tendon edges but also supply strength and support to the repair. Multiple techniques have been described, but none of them include another thread of suture. This could potentially increase the strength of the repair without affecting gliding.Methods: Caprine tendons were harvested, transected, and sutured with 6-0 Prolene. Four groups were created: single thread running (SR), single thread locking (SL), double thread running (DR), and double thread locking (DL). An Instron 5542 was used to pull the repaired tendons apart, and the energy at the break was calculated (gf/mm). For gliding resistance, we harvested a human A2 pulley. A pre- and postrepair value was obtained, and a ratio was elaborated. A single-factor analysis of variance and independent sample t tests were performed.Results: The SR group had a mean energy at break of 9339.71 ± 1630.212 gf/mm; the SL group, 9629.96 ± 1476.45 gf/mm; and the DR group, 9600.221 ± 976.087 gf/mm, with no statistical significance. The DL group was significantly higher at 14 740.664 ± 2596.586 gf/mm ( P < .05). When comparing SR with DL for gliding, SR had less than half of the resistance than DL (0.018 ± 0.004 and 0.049 ± 0.015 N/mm, respectively), with statistical significance ( P < .05).Conclusion: Using a single suture thread for running epitendinous repair is no different than locking with a single thread or using an extra thread in a running fashion. Performing a double suture thread with a locking technique is significantly stronger than the previously mentioned repairs, with the disadvantage of more resistance at the pulley.